IDENTIFYING THE CUSTOMER PERCEIVED VALUE ON VISIT INTENTION TOWARD KAMPUNG COKLAT TOURISM - Nisfullaili, Aulia; Wisesa, Anggara (Journal of Business and Management, 2018)
Abstract.The increase of tourism destinations in Indonesia, making the tourism sector as a key factor in job creation, business development, and infrastructure. This situation makes each region needs to develop the potential of the area to be a place of tourism which will help in the development of a better region. One of the potential tourism in Blitar Regency is Kampung Coklat Tourism located in Plosorejo Village, Blitar. Kampung Coklat tourism is an educational tour based on cocoa planting. Kampung Coklat already has many improvements such as expand the area, add more facilities, and others but Kampung Coklat’s ticket price is still the same because the owner assumes that the lower price is the dominant factor that builds customer visit intention. However, there is no research from them and their price strategy is based on their assumption, so it is necessary for the company to understand the customer perceived that actually influence the customer's visit intention. So the purpose of this research is to identify the customer perceived value towards visit intention in Kampung Coklat tourism. It uses five dimensions of Customer Perceived Value which are service quality (SQ), emotional value (EV), price (P), social value (SV), and reputation (R). This research uses the quantitative approach with the number of samples 384 visitors to Kampung Coklat. Then the author uses the Multiple Linear Regression to analyze the data which shows that 4 of five independent variables significantly affects the customer visit intention which are service quality, emotional value, social value, and price. Also, this research can prove that the price is the dominant dimension that affecting customer visit intention toward Kampung Coklat tourism. This research addressed to Kampung Coklat tourism in order to which value that customer dominant perceive so that the company will choose the best strategy to increase the number of customers, also to maximize the profit and still make an improvement to fulfill the customer need and wants. It also can be applied to other tourism in order to have a large number of visitors and can increase the regional economic movement and provide retribution for Indonesia.Keywords: Customer Perceived Value, Tourism, Service Quality, Emotional Value, Social Value, Price, Visit Intention